Предмет: Алгебра,
автор: mouse11
Решите уравнение
(4х + 3) - (10х + 11) = 7+ (13 - 4х)
(7 - 5х) - (8 - 4х) + (5х + 6) = 8
(3 - 2х) + (4 - 3х) + (5 - 5х) =12 + 7
Ответы
Автор ответа:
0
1) 4x-10x+4x=-3+11+7+13
-2x=28
x=-14
2) -5x+4x+5x=-7+8-6+8
4x=3
x=3/4
3) -2x-3x-5x=-3-4-5+12+7
-10x=7
x=-7/10
-2x=28
x=-14
2) -5x+4x+5x=-7+8-6+8
4x=3
x=3/4
3) -2x-3x-5x=-3-4-5+12+7
-10x=7
x=-7/10
Автор ответа:
0
4x+3-10x-11=7+13-4x
-6x-8=20-4x
-6x+4x=20+8
-2x=28
x=28:(-2)
x=-14
7-5x-8+4x+5x+6=8
4x+13=8
4x=8-13
4x=-5
x=5:4
x=1.25
3-2x+4-3x+5-5x=12+7
-10x+12=19
-10x=19-12
x=7:(-10)
x=0.7
-6x-8=20-4x
-6x+4x=20+8
-2x=28
x=28:(-2)
x=-14
7-5x-8+4x+5x+6=8
4x+13=8
4x=8-13
4x=-5
x=5:4
x=1.25
3-2x+4-3x+5-5x=12+7
-10x+12=19
-10x=19-12
x=7:(-10)
x=0.7
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Українська мова,
автор: seninakarina079
Предмет: Математика,
автор: VladXyligan
Предмет: Математика,
автор: Алька000